Effects of Nisin, Cecropin, and Penthorum chinense Pursh on the Intestinal Microbiome of Common Carp (Cyprinus carpio) - Ke, Famin; Xie, Peijuan; Yang, Yanrong; Yan, Liu; Guo, Ailing; Yang, Jian; Zhang, Jing; Liu, Li; Wang, Qin; Gao, Xiaowei (Frontiers in Nutrition, 2021)
Following a ban on antibiotic use in the feed industry, trials on the effects of various immunostimulants (prebiotics, probiotics, antimicrobial peptides [AMPs], and herbs) on the survival, growth, immunity, and disease control of farmed fish in aquaculture are being rapidly conducted. The wide variety of microbes with roles in nutrition, metabolism, and immunity in the fish intestine is the primary factor affecting the fermentability and functionality of dietary immunostimulants. For this reason, the dynamic interactions between immunostimulants and the intestinal microbiome may influence fish health. In this study, the effects of two agriculturally important AMPs (nisin and cecropin) and one herb (Penthorum chinense) on the gut microbiome of common carp were investigated, using 16S rDNA high-throughput sequencing. The results suggest that all three substances can alter the richness, diversity, and composition of the intestinal microbiota of common carp. P. chinense had a similar effect on the gut microbiota of common carp to that of nisin, and both promoted more striking changes in the gut microbiota community than did cecropin. The relative abundance of Proteobacteria was lower in the nisin and P. chinense groups than in the control and cecropin groups. The relative abundance of Bacteroidetes in the nisin, cecropin, and P. chinense groups was markedly increased, compared with that of the control group. Additionally, nisin, cecropin, and P. chinense showed obvious anti-inflammatory effects on the fish intestine, which was reflected by significantly increasing the expression levels of two anti-inflammatory cytokines IL-10 and TGF-β. Some digestive enzyme activities in the fish intestine were also significantly enhanced by supplementing these three substances in feeds.